x^3 + y^3 + z^3 = 3xyz
Edwin Clark
eclark at math.usf.edu
Mon Apr 24 18:29:58 CEST 2006
>
(*) x^3+y^3+z^3-3*x*y*z =
(x-z-z*alpha+y*alpha)*(x-y-y*alpha+z*alpha)*(z+x+y)
>
> where alpha is a root of x^2 + x + 1,
>
> any roots of x+y+z=0 will be a solution. ...
> ___________________________________________________
The only integer solutions are x=y=z and z = -x-y.
Suppose that x,y,z is another solution and x+y+z is not 0
then by the above factorization one of the other factors
must be 0. Say x-z-z*alpha+y*alpha = 0. Since alpha is
not a rational number, y-z = 0, that is, y = z and hence
also x=z. So x=y=z. If the other factor involving alpha
is 0 a similar argument shows x = y = z.
More information about the SeqFan
mailing list